أهمية اللغة العربية وتأثيرها في إندونيسيا - khoirurrijal khoirurrijal (Institut Agama Islam Negeri (IAIN) Metro, 2017)
The Arabic language has become a humanitarian message with itsconcepts and ideas, and managed to be the language of civilizedhumanity, and involving a wide variety of nations, includingIndonesia.The Arabic is the language of civilization in the world. It is theoldest languages still have the characteristics of words andstructures, drainage, and about literature and fiction with beingable to express different perceptions of science. It is also thelanguage of communication between millions of people scattered inthe prospects for the Earth, including Indonesia.The Arabic words in the Indonesian language are too numerous tocount. They have carried the message of Islam and the wording ofmany structures, semantics, and manynewvoices to express whatIslam brought from its concepts, ideas, systems and rules ofconduct, and became the language of religion, culture, civilizationand governance at the same time. The impacts of the Arabiclanguage in the Indonesian language are often through by thewords, the structures, the signs and the sounds